Anaesthetists' non-technical skills - Flin, R; Patey, R; Glavin, R; Maran, N (British journal of anaesthesia : BJA, 2010)
This review presents the background to the development of the anaesthetists' non-technical skills (ANTS) taxonomy and behaviour rating tool, which is the first non-technical skills framework specifically designed for anaesthetists. We share the experience of the anaesthetists who designed ANTS in relation to applying it in a department of anaesthesia, using it in a simulation centre, and the process of introducing it to the profession on a national basis. We also consider how ANTS is being applied in relation to training and research in other countries and finally, we discuss emerging issues in relation to the introduction of a non-technical skills approach in anaesthesia.